ASSESSMENT OF PLATELET REACTIVITY WITH CEREBRAL MICROEMBOLI IN CAROTID STENOSIS. Issue 12 (15th November 2016) - Kinsella, Justin; Tobin, Oliver; Tierney, Sean; Feeley, Timothy; Egan, Bridget; Coughlan, Tara; Collins, Ronan; O'Neill, Desmond; Harbison, Joseph; McCabe, Dominick
Abstract : Introduction: The relationship between 'high on-treatment platelet reactivity (HTPR)' and micro-embolic signals (MES) on transcranial Doppler ultrasound (TCD) has not been comprehensively assessed in carotid stenosis. Methods: This prospective, observational study assessed HTPR and MES in asymptomatic (N=31) versus 'early symptomatic' (≤4 weeks after TIA/ischaemic stroke; N=46) and 'late symptomatic' (≥3 months; N=35) ≥50% carotid stenosis patients. Longitudinal data from symptomatic patients were analysed. Platelet reactivity ex-vivo was assessed in whole blood with the PFA-100® (collagen-ADP and collagen-epinephrine [C-EPI] closure times). Bilateral, simultaneous MCA TCD classified patients as MES-positive or MES-negative. Results: There were no differences in HTPR prevalence between the overall asymptomatic and symptomatic groups. However, aspirin-HTPR prevalence was lower in 'late symptomatic post-intervention (N=10)' than asymptomatic patients (N=22) on aspirin (10% vs. 50% [C-EPI]; P=0.03). HTPR prevalence decreased in symptomatic patients between early and late phases (63% vs. 34%;P=0.017), including those on aspirin monotherapy (N=13; P=0.016). There were no differences in HTPR status in asymptomatic versus symptomatic MES-positive or MES-negative subgroups (p≥0.32). Discussion: Reduction in HTPR prevalence in symptomatic patients over time may reflect successful carotid intervention and/or acute phase response resolution. Larger studies should confirm whether therapeutic intervention(s) may reduce HTPR in symptomatic patients to enhance prevention.